Osseous anatomy of the pterygopalatine fossa. - Daniels, D L; Mark, L P; Ulmer, J L; Mafee, M F; McDaniel, J; Shah, N C; Erickson, S; Sether, L A; Jaradeh, S S (American Journal of Neuroradiology, 1998)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf